The perception of core job characteristics by Turkish employees, and its relation to job satisfaction - Rodopman, Aslı (My University, 1999)
This research aims to analyze the desired and actual levels of core job characteristics and their relation to job satisfaction among 124 Turkish employees. The job dimensions of skill variety, task identity, task significance, autonomy, and feedback have been specified to create an enriching job by Hackman and Oldham (1980) in their job characteristics model. Factor analysis of the current study came out with three dimensions which were named as 'freedom at work', 'significance by skills', and 'feedback'. 'Significance by skills' was the most, and 'feedback' was the least desired and experienced dimension. In accordance with the hypothesis, the correlation between each of the job dimensions and job satisfaction was significant. Being at least a high school graduate was found to be influential for the high correlation between the job dimensions and job satisfaction. Supporting another hypothesis, a significant negative correlation was found between the job satisfaction of employees and the difference between the desired-actual levels of job dimensions. The correlation of actual level of job dimensions to the 'internal' factors of the job satisfaction inventory was higher than their correlation to the 'external' factors. T-test and ANOVA analyses reveal that gender and position of employees were effective on the desired levels of job dimensions, but not on their actual experiences. The implications of these results for the design of enrichment programs in Turkey, and directions for future research are discussed.

Bu araştırma 124 Türk çalışanında, temel iş özelliklerinin istenen ve yaşanan düzeylerini ve bu özelliklerin iş tatmini üzerindeki etkisini incelemeyi amaçlamaktadır. Hackman ve Oldham (1980) 'iş özellikleri modeli' ile, beceri çeşitliliği, iş bütünlüğü, iş önemi, özerklik ve geribildirim boyutlarını iç kaynaklı motivasyonu oluşturan ve işi zenginleştiren özellikler olarak tanımlamışlardır. Bu araştırmada yapılan faktör analizi, 'iş içinde özgürlük', 'becerilerle önem' ve 'geribildirim' olarak adlandırılan üç boyut ortaya koymaktadır. Bu boyutlar göz önüne alındığında, 'becerilerle önemin' daha çok istendiği saptanmıştır. Yaşanan düzey incelendiğinde, 'geribildirim' in en az yaşanan boyut olduğu ortaya çıkmıştır. Araştırma hipotezini doğrular şekilde, iş boyutları ve iş tatmini arasında pozitif bir ilişki bulunmuştur. En az lise mezunu olmanın, bu ilişkiyi kurmakta etkili olduğu ortaya çıkmıştır. Bir diğer hipotezin öngördüğü gibi, çalışanların iş tatmini ile iş boyutlarının istenen-yaşanan düzey farkları arasında negatif bir ilişki bulunmuştur. Ayrıca, iş boyutlarının, iş tatmini ölçeğindeki iç kaynaklı faktörlerle olan ilişkisinin, dış kaynaklı faktörlerle olan ilişkisinden daha yüksek olduğu saptanmıştır. T-test ve ANOVA analizleri cinsiyet ve pozisyonun iş boyutlarının istenme düzeyleri üzerinde etkili olduğunu, ancak yaşanan, gerçek düzeyi etkilemediğini ortaya koymaktadır. Elde edilen sonuçların, Türkiye'deki iş zenginleştirme programlarına katkısı ve gelecek araştırmalara yönelik öneriler tartışılmıştır.
Keywords: İŞ TATMİNİ